Bringing the Solar System to Life: Interactive Morph-Based PowerPoint to Enhance Elementary Students’ Engagement - Nanaz Nur Fadillah; Yayan Carliyan; Ani Yanti Ginanjar; Djadjang Djuniardi (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to develop and evaluate Morph-based interactive PowerPoint learning media to enhance elementary students’ engagement in learning the solar system. Despite the growing use of digital learning media, limited studies have specifically examined Morph-based PowerPoint focusing on students’ multidimensional engagement, including behavioral, emotional, and cognitive aspects. This study employed a Research and Development (R&D) approach by integrating the ADDIE model with Sukmadinata’s development stages, including preliminary study, product development, and product testing. The participants consisted of 26 sixth-grade students. Data were collected using expert validation sheets, teacher observation sheets, and student response questionnaires and analyzed using descriptive percentage techniques. The findings indicate that the developed media achieved a feasibility score of 100% from both media and subject matter experts. Furthermore, student engagement reached 94% based on teacher observations and 96% based on student responses. These results demonstrate that Morph-based interactive PowerPoint media is effective in enhancing students’ engagement in learning the solar system and contributes to the integration of interactive visualization in elementary science learning.